ON THE MOMENTS OF THE 3-PARAMETER GOMPERTZ DISTRIBUTION - Hakiki, Moch Taufik; Adipradana, Dimaz Wisnu; Ahmad, Imam Safawi; Putri, Lahfanda Dista Permata (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
Gompertz distribution is a classical probability distribution extensively used in actuarial science, reliability, and survival analysis. Gompertz distribution also plays a role in various fields, such as biology, economics, and marketing analysis. Some extensions of this distribution have been studied and applied to various problems. In this article, we are concerned with some statistical properties of a 3-parameter Gompertz distribution. This extension of the Gompertz distribution introduced has been used in studying competing risk survival analysis. Our main results are the derivation of moments of this distribution and other statistical properties related to moments, such as moment generating function, mean residual life function, mean inactivity time and Lorenz curve. These results will serve as a complement to the theoretical aspect of the analysis of the distribution.